Soil nutritional status, not inoculum identity, primarily determines the effect of arbuscular mycorrhizal fungi on the growth of Knautia arvensis plants - Doubková, Pavla; Kohout, Petr; Sudová, Radka (Mycorrhiza, 2013)
Arbuscular mycorrhizal (AM) symbiosis is among the factors contributing to plant survival in serpentine soils characterised by unfavourable physicochemical properties. However, AM fungi show a considerable functional diversity, which is further modified by host plant identity and edaphic conditions. To determine the variability among serpentine AM fungal isolates in their effects on plant growth and nutrition, a greenhouse experiment was conducted involving two serpentine and two non-serpentine populations of Knautia arvensis plants grown in their native substrates. The plants were inoculated with one of the four serpentine AM fungal isolates or with a complex AM fungal community native to the respective plant population. At harvest after 6-month cultivation, intraradical fungal development was assessed, AM fungal taxa established from native fungal communities were determined and plant growth and element uptake evaluated. AM symbiosis significantly improved the performance of all the K. arvensis populations. The extent of mycorrhizal growth promotion was mainly governed by nutritional status of the substrate, while the effect of AM fungal identity was negligible. Inoculation with the native AM fungal communities was not more efficient than inoculation with single AM fungal isolates in any plant population. Contrary to the growth effects, a certain variation among AM fungal isolates was revealed in terms of their effects on plant nutrient uptake, especially P, Mg and Ca, with none of the AM fungi being generally superior in this respect. Regardless of AM symbiosis, K. arvensis populations significantly differed in their relative nutrient accumulation ratios, clearly showing the plant's ability to adapt to nutrient deficiency/excess.
Keywords: Symbiosis; Dipsacaceae; molekulární sekvence - údaje; houby; očkovadla agrotechnická; půda; Soil; Biomass; mykorhiza; symbióza; Agricultural Inoculants; Fungi; Mycorrhizae; fylogeneze; Phylogeny; biomasa; Molecular Sequence Data